Inequitable Enforcement: Introducing the Concept of Equity into Constitutional Review of Law Enforcement - Aviram, Hadar (2009)
This Article addresses a series of situations in which the exercise of police discretion, while passing current constitutional thresholds, seems unfair and unforeseeable. We call this problem inequitable enforcement. Current constitutional review of police action assesses all stops, searches, and arrests-regardless of how minor the offenseby focusing on the officer's level of suspicion and the officer's compliance with equal protection standards. In this Article, we argue that these existing constitutional mechanisms are flawed and fail to provide an appropriate remedy in cases of arbitrary and disproportionate enforcement for minor infractions. We begin by discussing the necessity of police discretion and the factors that guide officers in exercising it. After tracing the recent development of Fourth and Fourteenth Amendment law in the context of police discretion, we explain why these constitutional protections are inadequate for addressing the problem of inequitable enforcement. This inadequacy, we argue, is a result of the narrow and myopic lens through which the Supreme Court assesses reasonableness in its Fourth Amendment analysis, and discrimination in its Equal Protection analysis. We then suggest a set of considerations for assessing inequitability and present some ways in which those considerations can be integrated into constitutional doctrine. We conclude by discussing the promises and pitfalls of addressing inequitable enforcement through constitutional review